(untitled) (American Journal of Islam and Society, 2014)
This book is a valuable contribution to the growing body of research on the experiences and identities of British Muslim women. Intersections between gender, ethnicity, and Islam only became a prominent theme in British social sciences when the need for a careful and fair investigation of Muslim women’s realities arose during the last decade due to the unfolding of several Islamoriented policy debates (i.e., politicians’ critiques of the niqab) and the introduction of legislation designed to tackle “violent extremism” and “honor crimes.” The way these matters were represented in the media and policy documents has recycled and reinforced the age-old Orientalist stereotypes of Muslim women as silent and passive victims of patriarchal oppression. The author challenges these stereotypes, which are often expressed through depictions of Muslim women as spatially anchored and restricted. Thus this book focuses on cosmopolitan practices, particularly spatial and social transitions, among second-generation British Asian Muslim women. This approach brings together Bhimji’s earlier work, in particular articles dealing with these women’s online interactions focused on religion (2005), travelling to and belonging in South Asia (2008), and religious study circles (2009). The monograph is updated with new themes (e.g., case studies of prominent artists) and applies the analytic lens (viz., the concepts of spatialities and cosmopolitanism) adopted in her article on traveling overseas, to all of the issues discussed. The idea of these women crossing geographical, political, and social boundaries runs throughout the book in order to identify how the stereotype may be challenged. Bhimji demonstrates that cosmopolitanism, commonly understood as a rejection of localized identities in favor of global ones and which is based on social, cultural, and economic privilege, may also be interpreted as a willingness to cross boundaries and engage with difference. As boundaries and differences form a range of spaces, Bhimji builds her argument by utilizing a multi-method approach to her data. Not only does she engage in “traditional” ethnographic research with the women attending mosquebased study groups in northern England, as well as women who travel to South Asia and beyond, but she also includes media texts, online discussion transcripts, and case studies (i.e., a comedian, a poet, a visual artist, and a political ...